Serum Omentin-1 and CS846: Biomarkers for Diagnosis and Post-TKA Functional Outcomes in Knee Osteoarthritis - Qi, Yingzhao; Liu, Zhixin; Sun, Fengli; Liu, Ran; Deng, Jianfeng; Hao, Longfei; Wang, Jiayu; Gu, Juyuan (Journal of Medical Biochemistry, 2025)
Objective: To determine the synergistic diagnostic value of serum Omentin-1 and cartilage oligomeric matrix protein epitope CS846 (CS846) in knee osteoarthritis (KOA) and to explore their link to functional recovery following total knee arthroplasty (TKA), thereby contributing to improved early screening and prognostic strategies. Methods: We designed a prospective cohort study involving 84 subjects (42 with KOA and 42 healthy controls). The enzyme-linked immunosorbent assay (ELISA) technique was employed to measure serum Omentin-1, CS846, and inflammatory indices (hs-CRP and ESR). Receiver operating characteristic (ROC) curves determined diagnostic efficacy, and a logistic regression model was established for combined diagnosis. Functional outcomes, measured by WOMAC scores, and rehabilitation status was reviewed 6 months post-surgery. Results: Analysis revealed reduced Omentin-1 and elevated CS846 in KOA patients versus controls. The diagnostic performance (AUC=0.851) of the biomarker combination surpassed that of individual tests. Patients with KL1-2 grades exhibited elevated Omentin-1 but lower CS846 levels compared to those with KL3-4 grades (P<0.05). An inverse correlation was observed between Omentin-1 and inflammatory markers (hs-CRP, ESR), contrasting with the positive correlation for CS846. Post-treatment, poor recovery was associated with more pronounced decreases in Omentin-1 and increases in CS846 (P<0.05). The combined model effectively predicted suboptimal rehabilitation outcomes (AUC=0.857). Conclusion: The synergistic use of serum Omentin-1 and CS846 biomarkers boosts early detection capability for KOA while accurately forecasting post-TKA functional outcomes.